On Armando Liwanag et al's Harangues Against the First Congress of the NDF - Arguelles, Paco (Kasarinlan: Philippine Journal of Third World Studies, 2008)
Speech given by Paco Arguelles addressed to the National Democratic front (NDF) on April 23, 1993.